Pre-rainfall experiment calibration to determine droplet velocity at 15 different positions within an area of 1.21 m² - Gassen, Lisa; Esters, Leonie; Ribas-Ribas, Mariana; Wurl, Oliver (In: Gassen, L et al. (2024): Measurements of sea surface temperature and salinity in a large seawater basin under varying precipitation intensities and droplet characteristics [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964902, 2024)
We provide data from experiments with artificial rain over a 5100-liter basin with a retractable roof, where temperature and conductivity (to calculate salinity) were measured at different depths in the upper sea surface, as well as rain properties (intensity, rain temperature, droplet size and velocity). Three different nozzle types were used to investigate the impacts of droplet properties on temperature and salinity anomalies at the sea surface. To measure droplet sizes and velocities, we made calibration measurements with an optical laser disdrometer before the actual experiments. In the first experiments, we excluded external influences such as wind-driven mixing to show on a very small vertical and horizontal scale how very different rainfall intensities and properties such as droplet sizes and velocities affect sea surface temperature and salinity. In a second series of experiments, we used different stages of a flow pump to add turbulence to the basin and find out how quickly the rain water mixes with the seawater at the near-surface layer. The duration of the artificial rain was 15 minutes for all experiments. We used an acoustic doppler velocimeter (ADV) to calculate turbulent kinetic energy at two different depths (14 and 44 cm) within the basin. Additional samples from the sea surface microlayer (SML) were collected before and after the artificial rain in both experiments.
Keywords: droplet properties; mesocosm experiment; sea surface microlayer; Sea surface salinity; Sea surface temperature